Kepemimpinan Demokratis Kepala Sekolah Dalam Meningkatkan Prestasi Di Madrasah Aliyah Negeri Model Palangka Raya - Shanty bahar Ising; Mujiono Mujiono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to find out, describe and analyze the democratic leadership of the Principal in improving achievement at the Palangka Raya Model State Madrasah (MAN). The research method used is descriptive qualitative. The researcher wanted to describe the Principal's democratic leadership in improving achievement at the Palangka Raya Model State Islamic Senior High School (MAN). Primary data sources (person) are the Principal, Teachers (Teachers) and Students of MAN Model Palangka Raya. Whereas secondary data sources are the data in the Palangka Raya Model MAN and supporting literature. The results of the study show that the Principal's leadership in improving achievement in the Palangka Raya Model MAN is very democratic, this condition can be seen from: (1) Principals are happy to receive suggestions, opinions and even criticism from subordinates both delivered by students and teachers through suggestion boxes and in the teacher council meeting, (2) the Principal always strives to prioritize teamwork cooperation in an effort to achieve the goal by appointing the instructor teacher, trainer teacher and mentor teacher and conducting deliberation in planning, implementing and evaluating activities, (3) the Principal always tries to make subordinates more success than him, which is realized by including teachers in seminars, workshops, training and competitions so that they get achievements both locally and nationally, and (4) Principals always try to develop their personal capacity as good leaders in conceptual skills, human skill and technical skill.